Improvement on Coke Formation of CaO-Ni/Al2O3 Catalysts in Ethylene Production via Dehydration of Ethanol - Nurliyana, Masiran; Vo, Dai-Viet N.; Md. Abdus, Salam; Bawadi, Abdullah (Elsevier Ltd, 2016)
Carbon deposition during ethanol dehydration remains an issue that needs a conceivable solution as ethylene is coke-precursor for acidic-type catalysts. This research is focused on bimetallic CaO-Ni/Al2O3 catalyst to increase the resistance of coke formation on catalyst which mainly due to decomposition of carbon. Using wet impregnation procedure, various metal loadings of CaO and Ni (2-10wt%) were introduced onto